Tensions in World Literature Between the Local and the Universal (Springer Singapore, 2018)
This collection gives a diversified account of world literature, examining not only the rise of the concept, but also problems such as the relation between the local and the universal, and the tensions between national culture and global ethics. In this context, it focuses on the complex relationship between Chinese literature and world literature, not only in the sense of providing an exemplary case study, but also as an introspection and re-location of Chinese literature itself. The book activates the concept of world literature at a time when it is facing the rising modern day challenges of race, class and culture.